Aquatic Macrophyte Biomass Periodically Harvested Form Shipping Routes and Drainage Systems in a Selected Region of Poland as a Substrate for Biogas Production - Marcin Dębowski; Marcin Zieliński; Joanna Kazimierowicz; Maria Walery (Applied Sciences, 2023)
One of the identified obstacles to the development of biogas plants is the limited sources of organic substrates. Hydrophytes varying in morphology, chemical composition, and origin proved to be viable alternatives. This study’s aim was to determine the feasibility of deploying biomass from the cleansing of water reservoirs for anaerobic digestion. A mass and energy balance was estimated for Warmia–Mazury Province (Poland), the so-called Thousand Lake District. The effectiveness of anaerobic digestion was determined in anaerobic batch respirometric reactors. The biomass of hydrophytes harvested from this area approximated 38,070 Mg FM/year. The biogas yield from emergent plants approximated 350 m3/MgVS, and the average CH4 content of biogas reached 55%, whereas the respective values obtained from submerged biomass reached 270 m3/MgVS and 58% CH4. The total CH4 volume achievable from the facility fed with waste biomass of this type allows producing ca. 1,654,560 m3CH4/year, which enables reaching 866 kW theoretical thermal power and 636 kWe net electrical power with the facility. The contribution of biomass from mowing in this energy effect was about 84%, whereas that of the submerged vegetation obtained by hacking the bottom was 16%.